Structure Regulation of Bentonite-Alginate Nanocomposites for Controlled Release of Imidacloprid - Zhang, Haiyan; Shi, Yunsheng; Xu, Xiafan; Zhang, Min; Ma, Lin (ACS omega, 2020)
To reveal the structure and release properties of bentonite-alginate nanocomposites, bentonite of different amounts was incorporated into alginate by the sol–gel route. The structure of the composites was characterized by Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, and thermogravimetric analysis and related to the swelling property of the matrix and the release of imidacloprid. Bentonite was subject to exfoliation into nanoplatelets and combined into the polymeric network within alginate hydrogel, exhibiting profound effects on the structure features and release properties of the composites. Bentonite was of good compatibility with alginate due to the hydrogen bonding and the electrostatic attraction between them. The polymer chains were found to intercalate into the interlayer gallery of the clay. The high specific area of the nanoplatelets of bentonite benefited the intimate contact with alginate and reduced the permeability of the composites. However, in the composites with clay content of more than 10%, the polymer was insufficient to accommodate the silicate sheets completely. The aggregation of the platelets destroyed the structure integrity of the composites, facilitating the diffusion of the pesticide. The release of imidacloprid was greatly retarded by incorporating into bentonite-alginate composites and dominated by Fickian diffusion depending on the permeability of the matrix. The time taken for 50% of the active ingredient to be released, T 50, first increased and then decreased with increasing clay content in the composites, reaching a maximum around a weight percentage of 10%, at which the T 50 value for imidacloprid release was about 2.5 times that for the release from pure alginate formulation.